RELATION OF NUTRITION AND SALINITY TO GROWTH IN BLACK MOLLIES - MINBATTIWALLA, M. B.; GAZDAR, G. S. (Journal of Indian Fisheries Association, 2015)
Optimum growth, impaired growth and mortality in black molly arestudied in diluted sea water, sea water and also by introducing laboratorymprepared diets. Rapid acclimation in conjunction with enhanced growthcapacity was attained at 2%o concentration of common salt in water, and2%o and 5%o dilutions of sea water. 22%o protein content in the diet wasfound to be adequate for growth and fertility of fishes acclimated at asalinity of 2%o. Higher protein content and other nutritive elements werenecessary for fishes acclimated at 5%o and 14%o. Fertility was increased inseaswater dilutions rather than in common salt~water dilutions.